Effect of dust and shadow on performance of solar photovoltaic modules : Experimental analysis - Bhallamudi, Ramkiran; Kumarasamy, Sudhakar; Sundarabalan, Chinnayan Karuppaiyah (Tech Science Press, 2021)
This study presents an experimental performance of a solar photovoltaic module under clean, dust, and shadow conditions. It is found that there is a significant decrease in electrical power produced (40% in the case of dust panels and 80% in the case of shadow panels) and a decrease in efficiency of around 6% in the case with dust and 9% in the case with the shadow, as compared to the clean panel. From the results, it is clear that there is a substantial effect of a partial shadow than dust on the performance of the solar panel. This is due to the more obstruction of the sunlight by the shadowed area compared to the dust. The dust being finer particles for the given local experimental condition did not influence the panel than the shadow. The main outcome of this study is that the shadowing effect may cause more harm to the PV module than dust for the given experimental conditions. However, Further long-term studies on the effect of dust and shadow are needed to understand the effect on performance degradation and module life.